2018
DOI: 10.1007/s00418-018-1631-7
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate accumulation and perlecan/HSPG2 up-regulation in tumour tissue predict low relapse-free survival for patients with glioblastoma

Abstract: Glycosaminoglycans are major components of brain extracellular matrix (ECM), although heparan sulfate (HS) contribution in brain physiology and carcinogenesis remains underinvestigated. This study examined HS content and distribution in glioblastoma multiforme (GBM) tissues in the context of potential molecular mechanisms underlying its deregulation in brain tumours. Totally, 42 tissue samples and paraffin-embedded tissues for 31 patients with different prognosis were investigated. HS expression was demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
2
22
1
2
Order By: Relevance
“…It was shown that glioblastoma Grade IV possesses higher HS than astrocytoma Grade II [31]; HS content is present in patient-derived glioma tumor sphere cell lines and within the same tumor in a highly heterogeneous manner [32]. Increased HS content is demonstrated in GBM tumors and associated with low relapse-free survival of the GBM patients [4]. The obtained data on the decreased expression of HPSE in GBM tumors and the tendency of its negative correlation with HS content might suggest a possible molecular mechanism for HS upregulation in GBM tumors, along with other mechanisms involved in maintaining HS content in brain tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that glioblastoma Grade IV possesses higher HS than astrocytoma Grade II [31]; HS content is present in patient-derived glioma tumor sphere cell lines and within the same tumor in a highly heterogeneous manner [32]. Increased HS content is demonstrated in GBM tumors and associated with low relapse-free survival of the GBM patients [4]. The obtained data on the decreased expression of HPSE in GBM tumors and the tendency of its negative correlation with HS content might suggest a possible molecular mechanism for HS upregulation in GBM tumors, along with other mechanisms involved in maintaining HS content in brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are tightly involved in cell-cell and cell-matrix interactions as well as cell signaling, and their distortion by intensive chemoradiotherapy might be of importance for the residual GBM cells and their interaction with the surrounding brain tissue and relapse development. It was shown that HS is involved in glioma development, and its accumulation in GBM tumors is associated with low relapse-free survival for GBM patients [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В следу-ющих разделах мы приведем данные об участии ПГ в развитии тех типов опухолей, которые наиболее ин-тенсивно изучаются и в нашей лаборатории [61][62][63][64].…”
Section: функциональная роль протеогликанов при канцерогенезеunclassified
“…Furthermore, the higher expression of GPC1 has been suggested to predict poor prognosis of glioblastoma through examining the expression of GPC1 in 53 patients [20]. However, in another study with 31 cases, analysis showed no association between GPC1 expression and any clinical parameters of glioblastoma patients, including OS and tumor grade [21]. Collectively, these results suggest that GPC1 alone might be inappropriate to act as a strong and stable prognostic indicator for glioma, although GPC1 was implicated in the proliferation of glioma cells.…”
Section: Introductionmentioning
confidence: 99%